Theoretical Study of the Structural, Optoelectronic, and Reactivity Properties of N-[5′-Methyl-3′-Isoxasolyl]-N-[(E)-1-(-2-)]Methylidene] Amine and Some of Its Fe2+, Co2+, Ni2+, Cu2+, and Zn2+ Complexes for OLED and OFET Applications - Hilaire Tendongmo; Stanley Numbonui Tasheh; Didier Aymard Fouegue Tamafo; Fritzgerald Kogge Bine; Julius Numbonui Ghogomu (Journal of Chemistry, 2022)
Herein, we report the structural, electronic, and charge transfer properties of N-[5′-methyl-3′-isoxasolyl]-N-[(E)-1-(-2-thiophene)] methylidene] amine (L) and its Fe2+, Co2+, Ni2+, Cu2+, and Zn2+ complexes (dubbed A, B, C, D, and E, respectively) using the density functional theory (DFT). All molecules investigated were optimized at the BP86/def2-TZVP/RI level of theory. Single point energy calculations were carried out at the M06-D3ZERO/def2-TZVP/RIJCOSX level of theory. Reorganization energies of the hole and electron (λh and λe) and the charge transfer mobilities of the electron and hole (μe and μh) have been computed and reported. The λe and λh values vary in the order D > E > A > B > C > L and E > A > D > L > C > B, respectively, while μe and μh vary in the order B > C > L > A > E > D and C > B > A > L > E > D, respectively. μh of B (39.5401 cm2·V−1S−1) and C (366.4740 cm2·V−1s−1) is remarkably large, suggesting their application in organic light-emitting diode (OLED) and organic field-effect transistor (OFET) technologies. Electron excitation analysis based on time-dependent (TD)-DFT calculations revealed that charge transfer excitations may significantly affect charge transfer mobilities. Based on charge transfer mobility results, B and C are outstanding and are promising molecules for the manufacture of electron and hole-transport precursor materials for the construction of OLED and OFET devices as compared to L. The results also show that L and all its complexes interestingly have higher third-order NLO activity than those of para-nitroaniline, a prototypical NLO molecule.